Предмет: Алгебра,
автор: Vikaпррр
преобразуйте выражение в многочлен стандартного вида
a^2+(3a-b)^2
(3a-b)(3a+b)-b^2
(5c+7d)^2-10cd
x^3+(2-x)(x^2+2x+4)
Ответы
Автор ответа:
0
a²+(3a-b)²=a²+9a²-6ab+b²=10a²-6ab+b²
(3a-b)(3a+b)-b²=9a²-b²-b²=9a²-2b²
(5c+7d)²-10cd=25c²+70cd+49d²-10cd=25c²+49d²+60cd
x³+(2-x)(x²+2x+4)=x³+8-x³=8
(3a-b)(3a+b)-b²=9a²-b²-b²=9a²-2b²
(5c+7d)²-10cd=25c²+70cd+49d²-10cd=25c²+49d²+60cd
x³+(2-x)(x²+2x+4)=x³+8-x³=8
Похожие вопросы
Предмет: Физика,
автор: Griniov
Предмет: Физкультура и спорт,
автор: SailX
Предмет: История,
автор: emecaleksandra138
Предмет: Алгебра,
автор: petrenchik27